2018
DOI: 10.1111/ppe.12505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal marijuana exposure on neuropsychological outcomes in children aged 1‐11 years: A systematic review

Abstract: Background. Normalization of medicinal and recreational marijuana use has increased the importance of fully understanding effects of marijuana use on individual- and population-level health, including prenatal exposure effects on child development. We undertook a systematic review of the literature to examine the long-term effects of prenatal marijuana exposure on neuropsychological function in children aged 1–11 years. Methods. Primary research publications were searched from Medline, Embase, PsychInfo, CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 81 publications
(192 reference statements)
1
51
0
5
Order By: Relevance
“…Other studies demonstrated that rats prenatally and/or postnatally exposed to cannabinoids displayed motor hyperactivity at infancy and adolescence but not at adulthood (Bara et al, ; Mereu et al, ; Navarro et al, ; Silva, Zhao, Popp, & Dow‐Edwards, ). These preclinical studies are in line with human data showing that children of both sexes prenatally exposed to cannabis are hyperactive and impulsive starting around age 6 (Fried & Smith, ; Goldschmidt, Richardson, Cornelius, & Day, ; Sharapova et al, ). Altogether, the abnormal USV profile and locomotor activity displayed by WIN‐exposed male pups indicate the presence of sex‐specific deficits in social communication and locomotion at early life stages.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Other studies demonstrated that rats prenatally and/or postnatally exposed to cannabinoids displayed motor hyperactivity at infancy and adolescence but not at adulthood (Bara et al, ; Mereu et al, ; Navarro et al, ; Silva, Zhao, Popp, & Dow‐Edwards, ). These preclinical studies are in line with human data showing that children of both sexes prenatally exposed to cannabis are hyperactive and impulsive starting around age 6 (Fried & Smith, ; Goldschmidt, Richardson, Cornelius, & Day, ; Sharapova et al, ). Altogether, the abnormal USV profile and locomotor activity displayed by WIN‐exposed male pups indicate the presence of sex‐specific deficits in social communication and locomotion at early life stages.…”
Section: Discussionsupporting
confidence: 82%
“…showing that children of both sexes prenatally exposed to cannabis are hyperactive and impulsive starting around age 6 (Fried & Smith, 2001;Goldschmidt, Richardson, Cornelius, & Day, 2004;Sharapova et al, 2018). Altogether, the abnormal USV profile and locomotor activity displayed by WIN-exposed male pups indicate the presence of sex-specific deficits in social communication and locomotion at early life stages.…”
Section: Discussionmentioning
confidence: 99%
“…34 Animal studies revealed that even low levels of exposure to marijuana have adverse neurologic effects. 37 In a recent systematic review examining 7 longitudinal studies on the effects of prenatal exposure on neuropsychological function in children, investigators found varied results between the association of prenatal exposure to marijuana and a child's neuropsychological development at ages 1 to 11 years. The majority of studies demonstrated a negative impact of marijuana during pregnancy, including deficits in neuropsychological functioning, decreased attention, memory problems, and poor impulse control.…”
Section: Marijuana and Pregnancymentioning
confidence: 99%
“…[5][6][7][8] There is evidence that some women use cannabis to alleviate pregnancy-related symptoms (e.g., nausea and vomiting) and to self-medicate symptoms of depression, anxiety, or pain. 6,[9][10][11][12][13][14][15] However, due to concerns about health risks, including low infant birthweight and potential impacts on offspring neurodevelopment, [16][17][18][19] the American College of Obstetricians and Gynecologists currently recommends that pregnant women abstain from using cannabis during pregnancy and while breastfeeding. 20 An integrative review of women's perceptions of the health effects of prenatal cannabis use found that perceived harms of cannabis use in general are decreasing over time, 8 and some pregnant women who use cannabis perceive no health risks.…”
Section: Introductionmentioning
confidence: 99%